Usability Test Using the System Usability Scale in the Industrial Engineering Laboratory Universitas X Indonesia - Rowi, Saiful; Achmadi, Fuad (Jurnal Sains dan Aplikasi Keilmuan Teknik Industri (SAKTI), 2024)
In a quality education system, services are integral to delivering quality education. Providing excellent, effective, and efficient services to students is crucial for their success at the university, including laboratory services to support student practicum. However, the laboratory services in the Industrial Engineering Program Study at Universitas X in Indonesia seem to fall short of expectations and do not fully meet student needs. This study aims to assess the usability of the Industrial Engineering Laboratory services at Universitas X. The System Usability Scale (SUS) method is employed to gauge the service scale's effectiveness. The SUS score obtained in this study is 53, indicating that the services at the Industrial Engineering Laboratory Universitas X are categorized as acceptable but require improvement. Therefore, while the system created is deemed acceptable by its users, it needs enhancement to positively impact Industrial Engineering laboratory services.